Magnetic Fe3O4/polypyrrole‐salicylaldehyde composite for efficient removal of Mn (VII) from aqueous solution by double‐layer adsorption. Issue 28 (3rd May 2022) - Wang, Wenjiao; Ren, Jiajia; Wang, Chuanjin; Zheng, Mingming; Ma, Yong; Yin, Xunqian; Ding, Jianxu; Hou, Chunping; Li, Tingxi
Abstract: Fe3 O4 acted as the inner core, conducting polymer polypyrrole (PPy) was wrapped on the surface of Fe3 O4, and salicylaldehyde (SA) was grafted to prepare the Fe3 O4 /PPy‐SA composite. Fe3 O4 /PPy‐SA exhibited double adsorption properties for Manganese (Mn) (VII) from aqueous solution. And the adsorption properties were systematically investigated. The influences of pH, initial metal ion concentration and temperature on the adsorption performance were measured, showing that the optimal adsorption pH is 2. Moreover, it was found that the adsorption kinetics followed the pseudo second order model, the initial adsorption rate was 46.1467 mg/g/min, and the process was controlled by the liquid film diffusion. The Langmuir adsorption isotherm model could describe the adsorption process well, and the increase of metal ion concentration and temperature was beneficial to the adsorption process. At 288.15 K, the maximum equilibrium adsorption capacity was 471.6981 mg/g. Thermodynamic parameters indicated that the adsorption process was spontaneous, endothermic, and entropy increment. Meanwhile, the cycle test results showed that the adsorbent has good cycle performance and broad application prospects. Abstract :